2008
DOI: 10.2202/1935-1682.1862
|View full text |Cite
|
Sign up to set email alerts
|

Before and After: Gender Transitions, Human Capital, and Workplace Experiences

Abstract: We use the workplace experiences of transsexuals -individuals who change their gender typically with hormone therapy and surgery -to provide new insights into the longstanding question of what role gender places in shaping workplace outcomes. Using an original survey of a sample of male-to-female and female-to-male transsexuals, we document their earnings and employment experiences of transsexuals before and after their gender transitions. We find that while transsexuals have the same human capital after their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
111
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(118 citation statements)
references
References 54 publications
6
111
0
1
Order By: Relevance
“…For example, Schilt and Wiswall's (2008) study of forty-three trans individuals determined that average earnings for FtM transgender employees increased slightly following their gender transitions, while average earnings for MtF transgender employees fell by nearly one-third. This result is consistent with qualitative work demonstrating that for many MtF individuals, becoming a woman was often associated with a loss of authority in the workplace, harassment on the job, and termination; for FtM individuals, becoming a man was frequently associated with an increase in respect and authority (Dozier, 2005;Schilt, 2006 Roberts (2013) One of MacDonnell and Grigorovich's (2012) interviewees opined that 'Being trans gives me a unique position in the world and … I want that to be known' (p. 7).…”
Section: Outcomes For Business and Management Scholarshipmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Schilt and Wiswall's (2008) study of forty-three trans individuals determined that average earnings for FtM transgender employees increased slightly following their gender transitions, while average earnings for MtF transgender employees fell by nearly one-third. This result is consistent with qualitative work demonstrating that for many MtF individuals, becoming a woman was often associated with a loss of authority in the workplace, harassment on the job, and termination; for FtM individuals, becoming a man was frequently associated with an increase in respect and authority (Dozier, 2005;Schilt, 2006 Roberts (2013) One of MacDonnell and Grigorovich's (2012) interviewees opined that 'Being trans gives me a unique position in the world and … I want that to be known' (p. 7).…”
Section: Outcomes For Business and Management Scholarshipmentioning
confidence: 99%
“…A recent review of the scholarly literature on LGBT individuals in the workplace found that only 18 of the 263 journal articles identified in a systematic search (just under 7%) actually included transgender individuals in addition to lesbian, gay, and bisexual workers (McFadden, 2015). This exclusion of trans individuals has been attributed to difficulty in accessing a sufficient sample size (Schneider & Dimito, 2010), or the impossibility of collecting a genuinely random sample of transgender individuals, whose population is widely dispersed and often concealed (Schilt & Wiswall, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the transitioning goals, there are undoubtedly implications for transgender communities regarding the degree to which these communities are or are not seen by members as transitional and, moreover, the degree to which individuals desire to be out as trans or to "pass" as cisgendered (Schilt & Wiswall, 2008). In one study of 573 transgender women in Oakland and San Francisco, California, African American transgender women had the highest rate of hiding their transgender identity compared to all other races represented in the study (Nemoto et al, 2011).…”
Section: Transgender Identity and Minority Stressmentioning
confidence: 99%
“…Based on U.S. data, Schilt and Wiswall (2008) find an increase of earnings among female-to-male (FtM) transgender people after their gender transitions and a decrease of earnings among male-to-female (MtF) transgender people after their gender transitions, although their sample includes only 18 transgender workers who transitioned from male to female and 25 transgender workers who transitioned from female to male, as is acknowledged in their paper.…”
Section: Transgender Peoplementioning
confidence: 99%